Mejora de la calidad de la energía con sistemas fotovoltaicos en las zonas rurales - Rodríguez Gámez, Maria; Vázquez Pérez, Antonio; Velez Quiroz, Alcira Magdalena; Saltos Arauz, Wilber Manuel (Revista Científica, 2018)
The paper presents an analysis linked to one of the sustainable energy alternatives that are currently being adopted with worldwide success, in order to improve the quality of electricity service, save natural resources, reduce losses and contribute to the reduction of CO2 emissions into the atmosphere. The results of a study related to an application of technological innovation to improve the quality of the electric service in an isolated community are presented, by the introduction of photovoltaic technology connected to the low voltage network of a group of 20 houses that were studied. The results of the study of charge and hourly energy consumption of dwellings are shown and an own methodology for the design of the photovoltaic technology connected to the low voltage grid of the houses studied is shown, with potential to avoid the energy consumption of The conventional network, with the possibility of improving the quality of the electric service, while reducing the amount of the electric bill and reducing losses.